COMPARISON OF OSCILLATIONS OF SKIN BLOOD FLOW AND DEOXYGENATION IN VASTUS LATERALIS IN LIGHT EXERCISE - T. Yano; C-S. Lian; R. Afroundeh; K. Shirakawa; T. Yunoki (Termedia Publishing House, 2014)
The purpose of the present study was to compare oscillation of skin blood flow with that of deoxygenation in muscle during light exercise in order to determine the physiological significance of oscillations in deoxygenation. Prolonged exercise with 50% of peak oxygen uptake was performed for 60 min. Skin blood flow (SBF) was measured using a laser blood flow meter on the right vastus lateralis muscle. Deoxygenated haemoglobin/myoglobin (DHb/Mb) concentration in the left vastus lateralis were measured using a near-infrared spectroscopy system. SBF and DHb/Mb during exercise were analysed by fast Fourier transform. We classified frequency bands according to previous studies (Kvernmo et al. 1999, Kvandal et al. 2006) into phase I (0.005-0.0095 and 0.0095-0.02 Hz), phase II (0.02-0.06 Hz: phase II) and phase III (0.06-0.16 Hz). The first peak of power spectra density (PSD) in SBF appeared at 0.0078 Hz in phase I. The second peak of PSD in SBF appeared at 0.035 Hz. The third peak of PSD in SBF appeared at 0.078 Hz. The first peak of PSD in DHb/Mb appeared at 0.0039 Hz, which was out of phase I. The second peak of PSD in DHb/Mb appeared at 0.016 Hz. The third peak of PSD in DHb/Mb appeared at 0.035 Hz. The coefficient of cross correlation was very low. Cross power spectra density showed peaks of 0.0039, 0.016 and 0.035 Hz. It is concluded that a peak of 0.016 Hz in oscillations of DHb/Mb observed in muscle during exercise is associated with endothelium-dependent vasodilation (phase I) and that a peak of 0.035 Hz in DHb/Mb is associated with sympathetic nerve activity (phase II). It is also confirmed that each peak of SBF oscillations is observed in each phase.